Studi Korelasi Variasi Suhu Udara, Titik Embun, Tekanan Udara terhadap Gaya Angkat Pesawat dengan Mempertimbangkan Komponen Angin Di Bandara Internasional Kualanamu - Sianturi, David Karunia; Hutahaean, Kevin; Haryanto, Yosafat Donny (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study analyzes the correlation between variations in air temperature, dew point, and air pressure on aircraft lift force while considering wind components at Kualanamu International Airport using a quantitative descriptive-correlational approach based on observational METAR and SPECI data throughout 2024. The analyzed parameters included air temperature (°C), dew point (°C), air pressure (hPa), wind direction (°), and wind speed (knot), with lift force calculated based on Boeing 737-800 specifications. The results show that air temperature has a consistent positive correlation with lift force throughout the year (r = 0.35-0.6) with the highest value in April (r = 0.603) and the strongest correlation in the temperature range of 28-33°C, dew point shows variable correlation patterns between months (r = -0.301 to 0.603), while air pressure shows consistent negative correlation (r = -0.1 to -0.47) with the strongest correlation in July (r = -0.472) in the pressure range of 1003-1010 mb. The research concludes that air temperature is the most influential meteorological parameter on aircraft lift force with stable positive correlation, while wind components (headwind/tailwind) have relatively small effects on lift force for large commercial aircraft.